Early commercial experience with a newly designed balloon-expandable transcatheter heart valve: 30-day outcomes and implications of preprocedural computed tomography. (30th November 2020) - Schaefer, Andreas; Plassmeier, Fabienne; Schofer, Niklas; Vogel, Lukas; Ludwig, Sebastian; Schneeberger, Yvonne; Linder, Matthias; Demal, Till; Seiffert, Moritz; Blankenberg, Stefan; Reichenspurner, Hermann; Westermann, Dirk; et al.
Abstract: OBJECTIVES: We herein report a single-centre experience with the SAPIEN 3 Ultra balloon-expandable transcatheter aortic valve implantation (TAVI) system. METHODS: Between March 2019 and January 2020, a total of 79 consecutive patients received transfemoral TAVI using the SAPIEN 3 Ultra device. Data were retrospectively analysed according to updated Valve Academic Research Consortium-2 definitions. Detailed analysis of multislice computed tomography data was conducted to identify potential predictors for permanent pacemaker (PPM) implantation and residual paravalvular leakage (PVL) post TAVI. RESULTS: Device success and early safety were 97.5% (77/79) and 94.9% (75/79) with resulting transvalvular peak/mean pressure gradients of 21.1 ± 8.2/10.9 ± 4.4 and PVL >mild in 0/79 patients (0%). Mild PVL was seen in 18.9% (15/79) of cases. Thirty-day mortality was 2.5% (2/79). The Valve Academic Research Consortium-2 adjudicated clinical end points disabling stroke, acute kidney injury and myocardial infarction occurred in 1.3% (1/79), 5.1% (4/79) and 0% (0/79) of patients. Postprocedural PPM implantation was necessary in 7.6% (6/79) of patients. Multislice computed tomography analysis revealed significantly higher calcium amounts of the right coronary cusp in patients in need for postprocedural PPM implantation and a higher eccentricity index in patients with postinterventional mild PVL. CONCLUSIONS: First experience with this newly designed balloon-expandable-transcatheter heart valve demonstrates adequate 30-day outcomes and haemodynamic results with low mortality, low rates of PPM implantation and no residual PVL >mild. The herein-presented multislice computed tomography values with an elevated risk for PPM implantation and residual mild PVL may help to further improve outcomes with this particular transcatheter heart valve in TAVI procedures. Abstract : Transcatheter aortic valve implantation (TAVI) is an established therapy for severe aortic valve stenosis in patients with an intermediate- or high-risk profile for surgical aortic valve replacement, when a suitable anatomy for the interventional approach is present [1–3].